2012
DOI: 10.1158/1078-0432.ccr-11-2000
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Cognitive Function and Hippocampal Neurogenesis following Cancer Chemotherapy

Abstract: Purpose: A substantial proportion of breast cancer survivors report significant, long-lasting impairments in cognitive function, often referred to as "chemobrain." Advances in detection and treatment mean that many more patients are surviving long-term following diagnosis of invasive breast cancer. Thus, it is important to define the types, extent, and persistence of cognitive impairments following treatment with cytotoxic cancer drugs.Experimental Design: We examined the effects of chronic treatment with two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
204
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 246 publications
(229 citation statements)
references
References 45 publications
15
204
2
3
Order By: Relevance
“…To evaluate the outcome of MV transplantation on cognitive function, rats from each group were subjected to cognitive testing 1 mo after transplantation surgery. Cognitive testing was conducted over 3 wk and included four different open arena tasks followed by contextual and cued FC as described in detail previously (8,30).…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the outcome of MV transplantation on cognitive function, rats from each group were subjected to cognitive testing 1 mo after transplantation surgery. Cognitive testing was conducted over 3 wk and included four different open arena tasks followed by contextual and cued FC as described in detail previously (8,30).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, a combination of the following terms was used: "physical inactivity", "bed rest", "immobilization", "lack of exercise" and on the Citation: Pesendorfer LM, Zimmer P, GalvĂŁo DA, Bloch W, Baumann FT (2016) Impact of Physical Inactivity on the Multifactorial Process of Developing Cancer-Related Cognitive Impairments. J Cancer Sci Ther 8: 222-227. doi: 10.4172/1948-5956 changes might be associated with impaired memory performance and difficulties in learning [4,5,[22][23][24][25][26][27]. In rodent research, it is also reported that cytostatic agents (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…As such, a second search was conducted focusing on influence of physical inactivity on cognitive performance in general. Therefore, a combination of the following terms was used: "physical inactivity", "bed rest", "immobilization", "lack of exercise" and on the changes might be associated with impaired memory performance and difficulties in learning [4,5,[22][23][24][25][26][27]. In rodent research, it is also reported that cytostatic agents (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations